Assessment of Certain Hematological Indices and Interlukin-6 in Workers and Individuals Who Live Near to Crude Oil Wells in Middle Petroleum - Mariam.R. Alghara; Ausama Ayob Jaccob; Azza.Sajid. Jabbar (College of Pharmacy University of Baghdad, 2023)
Environmental exposures to a variety of pollutant elements especially fuel waste products may result in harmful impacts on several physiological systems. The inflammatory response and the hematological system are the major affected systems. The aim of the study is to reveal the impact of oil exposure on several hematological parameters and IL-6 of oil workers and to detect which parameters are more affected as prognosticators for clinical disorders. This study included three groups, 50 persons in each. Control group; Group1 workers at oil wells; and Group2 who live close to oil wells. Physical parameters, serum interleukin 6 , random blood glucose , hematological parameters are measured. Significant rise in pulse rate, serum interleukin 6 and RBG were documented in workers. Hematological parameters were adversely affected by air pollution . We found a significant rise in platelet count in Group 1 patients . The correlation between IL-6 and certain hematological indices revealed that each of WBC and platelets were significantly correlated to IL-6. In conclusion People work or lived close to oil wells area showed alterations in hematological and inflammatory parameters may be related to continuous exposure to petrol fumes, which also results in a considerable increase in interleukin-6. Keyword:Oil wells, hematological indices, interleukin 6.